Adakah Kepalsuan Hukum di Dalam Hukum Kepailitan Indonesia? (Suatu Penghindaran Terhadap Kepalsuan Hukum) - FL. Yudhi Priyo Amboro (Jurnal Selat, 2016)
Indonesia has a legal tradition from Dutch Law. One of it is Bankruptcy Law, which is Staatsblad 1905 No. 217 jo. Staatsblad 1906 No. 348. In 1998, when Indonesia faced the economic crisis, through IMF’s demand, Indonesia had to make any revisions on that Bankruptcy Law, and become the Act No. 4 Year 1998. There some problems occurred when Act No. 4 Year 1998 was implemented then it changed become Act No. 37 Year 2004. One of the big problems which became the trigger was the case of Prudential Insurance, which was stated bankrupt by the court. This writing has a goal to pierce or detect the interests which might appear among the process of those Bankruptcy Law revisions, whether or not there is a falsifity of law indication. This is a legal research which use secondary data and analyze with deductive method. Keywords : Indonesian Bankruptcy Law, Falsifity of Law.